Preservation of Antagonistic Activity of Free Probiotics and Those Immobilized on Enterosorbents After Low Temperature Storage - Babinets, Olga M.; Vysekantsev, Igor P.; Martsenyuk, Valentina F. (Problems of Cryobiology and Cryomedicine, 2014)
N/A Probl Cryobiol Cryomed 2014; 24(2):172.